An authoring tool to provide groups and crowds animation using Natural Language scripts - Mainardi, Guido; Normoyle, Aline; Cassol, Vinícius; Badler, Norman; Musse, Soraia Raupp (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2021)
Virtual environments have become ubiquitous, expanding beyond games into the domains of architecture, engineering, psychology, education, and archaeology. Furthermore, virtual humans can further enhance these environments when they provide compelling and coherent behaviors. In this paper, we present a scripting language based on simple, plain English commands. Our system assists people without game and animation expertise to populate large environments and complex scenarios. To validate our approach, we develop a prototype using Unreal Engine 4 and author a variety of indoor and outdoor agent simulations. Furthermore, we test our prototype with both experienced and inexperienced users, creating scenarios for a residence, mall, psychology scenario, and archaeological site.